(untitled) - 1962-; Levine, Arthur A.; ClGement, FrGedGeric (New York, 1994)
An artistic young boy's love for drawing cats gets him into trouble and leads him to a mysterious experience. Based on a Japanese legend.
Keywords: Folklore; Japan; Cats; Folklore